PENGARUH EFEK EKSTRAK ETANOL DAUN MURBEI (Morus multicaulis) SEBAGAI ANTIOKSIDAN PADA PARU – PARU TIKUS (Rattus norvegicus) JANTAN YANG DIPAPAR ASAP ROKOK DENGAN PARAMETER HISTOPATOLOGI - Muhammad Asri; Rachmat Kosman; Dewi Yuliana (Fakultas Farmasi UMI, 2015)
This research aimed to see antioxidant effect of extract ethanol leaves of Murbei (Morus multicaulis) in the lung hispathology of rats who get cigarette smoke exposure. The research method is have been done with experimental, 25 male rats (Rattus norvegicus) with 2-5 month old, body weigh range 100-200 gram were treated for 31 days. Devide in to 5 groups, P1 positive control (has given food and drink), P2 negative control (with cigarette smoke exposure), P3 (a group treated by cigarette smoke exposure and extract ethanol Murbei 100 mg/kgBB), P4 (a group treated by cigarette smoke exposure and extract ethanol Murbei 200 mg/kgBB), P5 (a group treated by cigarette smoke exposure and vitamin E 1,8 mg/kgBB). In 31st day, the mice performed surgery to retrieve organs rat lung histopathology test is then performed. Given ethanol extract of leaves of Murbei (Morus multicaulis) 100 mg/kgBB and 200 mg/kgBB may have an effect as an antioxidant in the lungs of rat (Rattus norvegicus) males